Pusa Long Green – A high yielding cucumber variety for spring summer and kharif season - Munshi, D; Behera, T K; K Sureja, Amish; Singh, J; Tomar, B S (Indian Horticulture, 2022)
Pusa Long Green is an early long fruited, improved variety of cucumber for spring-summer and kharif seasoncultivation, developed by IARI for Zone IV (Sub-humid Sutlej-Ganga Alluvial Plains, i.e. Punjab, Uttar Pradesh, Bihar and Jharkhand). Apart from superior quality characters, it showed 34.93% higher yield over the National check variety Pant Khira-1